Clementina de Jesus: um corpo cultural, ancestral e da indústria cultural - Silva, Carlos Alberto Silva da (2016)
The object of this research is Clementina de Jesus’s song and ancestry, seen here as both aesthetic and political resistance within cultural industry. The analysis departs from theoretical and critical framework, provided by Cultural Studies, in particular the studies on both black culture and ancestry. This perspective helps place Clementina de Jesus within the Brazilian popular music scene as a memory of Africanity of slavery times, thus reaching both entertainment and music industry as the past within the present, the old within the new, tradition within modernity. In order to bridge this temporal passage, the researcher has resorted to cultural theorists, who are able to provide theoretical foundation to black diaspora and, consequently, to black culture, with a look at the Afro-Brazilian subject. Addressing Africanity, anteriority and religiosity of African descent means dealing with African mythology, which includes the Orishas, the myths, the magic and the spell. Clementina de Jesus emerges in the world of cultural industry supported by a part of the black song and music marked by the colonizing, slaving and classist processes of the Brazilian History. Therefore, the thesis prints on Clementina de Jesus the resistance to the erasure of History, which has, strategically, created a musical black brand among other cultures. Ancestry may be understood as a category of relationship, link, inclusion, diversity, unity and spell (Oliveira, 2007). Such na idea helps us understand that Clementina de Jesus worked, and still works, as political weapon in the defense of black culture. In a way, his ancestral son was not reduced to bringing to the scene the orality of the ‘Senzala’ times, which had been left aside at the risk of being forgotten. She has also served as a political strategy of insertion within cultural industry.